PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR EKONOMI SISWA KELAS XI SMA NEGERI 5 PEKANBARU - Jumraini Jumraini (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
The background of this study is the low level of economic learning outcomes of students of class XI SMA Negeri 5Pekanbaru, low student learning outcomes is seen from the average learning outcomes obtained by students is59,40. The low acquisition of student learning outcomes done efforts to improve learning outcomes by applying themodel NHT type cooperative learning. This study is a classroom action research conducted in class XI SMA Negeri5 Pekanbaru with the number of students as many as 40 students, this research conducted two cycles consisting oftwo meetings and two daily test, this research was conducted through four stages: planning, observation, andreflection. Based on the research data, it can be concluded that the implementation of cooperative learning modeltype NHT can improve student's economic learning outcomes, seen from the acquisition of learning data data on theaverage data of student learning outcomes of 59,40, in the first cycle has increased with the acquisition of 69,60,and in the second cycle increased with the acquisition of 75,80. In addition, the number of student completeness alsoincreased, in the initial data the number of completed students amounted to 17(42,50%), in the first cycle increasedby the number 25 (62,50%), and in the second cycle increased by the number 33 (82,50%)